Personality Traits and Weight Loss Maintenance: A Cross-Sectional Study - Koutras, Yiannis; Chrysostomou, Stavri; Giannakou, Konstantinos; Kosmidis, Mary H.; Yannakoulia, Mary (Frontiers in Nutrition, 2021)
Purpose: This cross-sectional study was based on the Cypriot cohort of the MedWeight study and examined differences between maintainers and regainers regarding personality traits. Methods: Participants were men and women who reported being at least overweight and experienced an intentional weight loss of ≥10% of their maximum weight, at least 1 year before participation. Assessment of personality, diet and physical activity was conducted through validated questionnaires and with 24 h recalls. Results: Findings from logistic regression analysis indicated that the odds of maintaining weight loss increased to 50% for agreeableness and decreased to 20 and 7% for perseverance and motor impulsiveness, respectively. Conclusion: Specific aspects of personality and impulsivity are relevant to weight loss maintenance and need to be considered when developing weight management interventions.